ANALYSIS OF HUMAN RESOURCES MANAGEMENT IN REGIONAL OFFICE VI BKN MEDAN - Mega Safitri; Nuri Aslami (Transpublika Publisher, 2022)
The purpose of this study is to describe and analyze human resource management using IPASN (Professional Index of State Civil Apparatus) indicators, which include educational qualifications, competencies, performance, and discipline for ASN (State Civil Apparatus) personnel at Regional Office VI BKN Medan. The research is being conducted on Regional Office VI BKN Medan. The qualitative descriptive methodology was employed in this investigation. Regional Office VI BKN Medan has performed admirably in terms of human resource management. Human resource management strategy development, as well as vision and mission statements, are carried out in accordance with business requirements. Control utilizing multiple media and stage selection to achieve human resources certified to the ISO 9001 standard in 2015. At Regional Office VI BKN Medan, human resource management is carried out by performing management functions such as planning, organizing, mobilizing, and supervising, although not all of them can be implemented. One of them is budget planning, which is not is not accommodated every year.